Hot working guide : a compendium of processing maps - Prasad, Y. V. R. K.; Sasidhara, S. (ASM International, 2015)
This ia a source book with flow stress data for hot working, processing maps with metallurgical interpretation and optimum processing conditions for metals, alloys, intermetallics, and metal matrix composites. In the first (1997) edition, processing maps for 162 materials were presented. Since that time, processing maps for another 130 materials with different initial conditions have been published in the literature. This edition has significant additions of maps on stainless steels, magnesium, titanium and nickel alloys. In compiling the second edition, stress-strain curves were not included since their shapes do not lead to clear conclusions on the mechanisms. However, the flow stress data are included since they are valuable in formulating constitutive equations required for finite element simulation. -- Edited summary from book.
Keywords: Metals -- Hot working.; Alloys -- Mechanical properties.; Metals -- Formability.; elektronické knihy; electronic books